Electric Field Analysis of XLPE Under Normal and Contamination Conditions using Comsol Multiphysics - Mohd Nasir, Muhammad Fakhrul Aqiuddin; Mohd Jamail, Nor Akmal; Qamarul Ezani Kamarudin (Evolution in Electrical and Electronic Engineering, 2025)
Cross-linked polyethylene (XLPE) cables are extensively used for power transmission and distribution due to their superior resistance to heat, moisture, and chemicals, making them ideal for challenging environments such as underground or underwater installations. However, power cables carrying over 100kV often face technical issues, including ageing, mechanical failures, insulation moisture, and current overloading, which can degrade the dielectric strength of XLPE cables over time. This study aims to determine the mass and relative permittivity of XLPE under normal and contaminated conditions and to analyze the electric field intensity characteristics using COMSOL Multiphysics software. Four samples were examined: Sample 1 (Virgin XLPE), Sample 2 (Distilled Water absorption), Sample 3 (Distilled Water and Iron Oxide), and Sample 4 (Distilled Water and Calcium Carbonate), with the latter three immersed in distilled water. Using Keysight 16451B, relative permittivity values were measured, and electric field intensities were simulated with COMSOL Multiphysics. Results indicated that Sample 1 (Virgin XLPE) exhibited the highest electric field intensity at 4.7453 MV/m in the sphere-sphere configuration, while Sample 2 recorded 4.7054 MV/m, Sample 3 showed 4.7104 MV/m, and Sample 4 had 4.7196 MV/m. These findings suggest that the maximum electric field intensity is influenced by the permittivity of the XLPE, with variations attributed to the presence of moisture and other materials, altering the dielectric properties and causing localized oscillations in the electric field distribution. This study underscores the importance of environmental factors in applying and maintaining XLPE cables, highlighting the need for regular monitoring and assessment to ensure optimal performance and longevity.